Spatial Analysis of the Effect of Aspergillus spp Fungus on the Soil of the Plateau (Najaf - Karbala) - Al-Salami, Maryam A. Rahim; Menkhi, Saadia Akol (South Eastern European Journal of Public Health, 2024)
This study investigated the spatial and temporal variation of Aspergillus spp fungus in the soil of the Najaf-Karbala plateau, covering Najaf district center and Al-Haidariya district. Soil samples were collected from 36 sites over four seasons and analyzed microbiologically to identify types and quantities of Aspergillus spp fungus. Spatial analysis techniques, including GIS and spatial autocorrelation, were used to examine the distribution of Aspergillus spp fungus across the study area. The results showed significant spatial and temporal variation in the occurrence of Aspergillus spp fungus, with highest concentrations found in autumn and spring seasons. The study highlights the environmental hazard posed by Aspergillus spp fungus in the Najaf-Karbala plateau soil, with potential health risks for humans, animals, and plants. Further research is needed to understand the sources and drivers of Aspergillus spp fungus presence and to develop strategies for mitigating its environmental and health impacts.